(untitled) (Journal of Laboratory Animal Science, 2019)
Five cases of malocclusion were reported in 3-5 months old Wistar rats (male – 3, female - 2). Clinical history indicated that though these animals were maintained under standard laboratory/husbandry practices, since a month were anorectic, loosing weight and became lethargic/dull. Careful examination of buccal cavity showed increased length of lower / upper incisor teeth (1.5-2.5 cm) protruding outside the mouth and mild to moderate degree of congestion and erosions on buccal mucosa. Possible etiology could not be ascertained in these cases but younger age of the rats was suggestive of its congenital origin as against spontaneous.